Design, Simulation, and Testing of Active Cooperative Control Strategies for a Light Sensation Transfer Nursing Robot - Yuansheng Ning; Lingfeng Sang; Zhengcai Wang; Bianca Ghinoiu; Fuqiu Lu; Hongbo Wang; Luige Vlădăreanu (Actuators)
The transfer of patients, especially elderly or long-term bedridden individuals, has emerged as an important problem due to the growing aging population. The advancement of transfer nursing robots provides an intelligent solution to this problem. This paper presents a Parallel Master–Slave Cross-Coupled (PMSCC) cooperative control strategy based on adaptive fuzzy controllers to address the motion control challenges of a self-developed light Sensation Transfer Nursing Robot (LSTNR). First, the working principle of the LSTNR is introduced, followed by the establishment of its motion model. Next, the robot’s velocity is designed based on PMSCC cooperative control strategies, with an adaptive fuzzy controller performing motion control. Finally, the proposed cooperative control strategy is simulated and analyzed, and the robot is tested for patient transfer. The results show that the proposed control strategy reduces the velocity cooperation error between the robot’s motors. The average velocity error of the robot is reduced by 92.69%, 92.08%, 47.35%, and 87.78%, respectively, compared to the non-cooperatively controlled robot. This significantly addresses issues such as belt slack, tightness, and patient position deformation during operation, improving the transfer efficiency and effectiveness of the LSTNR.